Pouwłaszczeniowy ruch chłopski - podobieństwa i różnice z ruchem antyfeudalnym - Kostrzewska, Maria (Acta Universitatis Lodziensis. Folia Historica, 1995)
The problem was discussed on the examples of five gubernyas of the Polish Kingdom (Warszawa, Lublin, Kielce, Piotrków and Radom) from 1840’s to 1904. They paid attention to the problem of continuity and changes taking place in peasants’ activities before and after enfranchisement. The characteristic feature of peasants’ movement was refering to the past and using the earlier acquired experience. The forms and methods of peasants’ acting were mostly determined by tradition whereas the aim of their demands and manifestations depended on general conditions in which they used to live and it changed with them. On the whole, however, the reality surrounding the peasants made them manifest their discontent and the sense of injustice. The superior aim of peaseants’ acts was striving after getting the right to their land and, after acquiring it, preserving and broadening their state of possesion. It was followed by an interst in general and agrarian education and after the communal reform in self governed matters. The analysis of the peasants’ statements and behaviours seem to confirm the thesis about broadening their horizons of thinking and acting. Gradually they gave, up the already worked out in villein period forms of fighting and destroying the existing social-economic structures, entering the way of positive acts. They were expressed by striving after organized schools and associations and by reading development, selfeducation and a growing interest in the works of the commune. The problems of education and social-economic activity were connected with peasants’ manifestations in defence of the Polish character. The January Uprising and russification growing after its decline caused peasants’ resistance and increase of national aspirations. Decidedly negative attitude of peasants towards the invader was reflected in the Revolution of 1905-1907. However, it did not appear suddenly but it grew gradually and sometimes it reached the times of antifeudal movements.